Inside Cover: Molecular Assembly Line: Stepwise Hydrogenation of Multifunctional Substrates over Catalyst Mixtures (ChemCatChem 3/2016). Issue 3 (February 2016) - Tomkins, Patrick; Gebauer‐Henke, Ewa; Müller, Thomas E.
Abstract : The Cover shows the principle of a molecular assembly line for the hydrogenation of nitrobenzene over catalyst mixtures of carbon‐nanotube‐supported platinum and carbon‐nanotube‐supported ruthenium. In their Full Paper, Tomkins et al. investigate the step‐wise hydrogenation of nitrobenzene via aniline to cyclohexylamine. Each catalyst, Pt/CNT and Ru/CNT, by itself is well suited for a specific step of the consecutive reaction. Using a mixture of both catalysts in one pot resulted in superior rates for the hydrogenation reactions. The effect was most pronounced, when a small quantity of Pt/CNT was combined with Ru/CNT as the more abundant catalyst. The study stimulates a new avenue for catalyst development for consecutive multi‐step reactions. More information can be found in the Full Paper by Tomkins et al. onpage 546 in Issue 3, 2016 (DOI:10.1002/cctc.201500988 ).